2007
DOI: 10.1016/j.tox.2006.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nitric oxide has protective effect on fumonisin B1 hepatotoxicity in mice via modulation of sphingosine kinase

Abstract: Fumonisin B 1 , a natural mycotoxin, is an inhibitor of ceramide synthase causing marked dysregulation of sphingolipid metabolism in cells. This mycotoxin causes accumulation of free sphingoid bases (sphingosine and dihydrosphingosine or sphinganine) and their metabolites, important messengers involved in signal transduction leading to either cell survival or death. Free sphingoid bases are known apoptotic molecules whereas their respective 1-phosphates are protective. We previously reported that fumonisin B 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Another study showed that preventing ceramide formation in monocytes by inhibiting neutral sphingomylinase with C11AG, a selective inhibitor, led to blocking the translocation of NF-kB and the induction of iNOS (27). Since the SK1/S1P pathway has been implicated in NF-kB activation (28) and iNOS induction (29) these studies suggest that previous findings attributed to sphingosine and ceramide on innate stimulation are possibly due to their intracellular metabolism to S1P.…”
Section: Discussionmentioning
confidence: 61%
“…Another study showed that preventing ceramide formation in monocytes by inhibiting neutral sphingomylinase with C11AG, a selective inhibitor, led to blocking the translocation of NF-kB and the induction of iNOS (27). Since the SK1/S1P pathway has been implicated in NF-kB activation (28) and iNOS induction (29) these studies suggest that previous findings attributed to sphingosine and ceramide on innate stimulation are possibly due to their intracellular metabolism to S1P.…”
Section: Discussionmentioning
confidence: 61%
“…These figures are the first model combining changes in lipid subspecies and gene expression that highlights how Huh7 cells respond and adapt to the disruption of ceramide synthesis. Previous studies focused on the effects of altering SPTLC functions on cholesterol efflux (14), apoE secretion (37), necrosis (38), and inflammation (39). The changes observed in lipid synthesis clearly indicate that inhibiting SPTLC123 by siRNA-mediated knockdown is sufficient to reduce ceramide synthesis and alter certain subspecies (mainly C16:0) of other lipid classes, especially phospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the fact that FTY720 resembles sphingosine (Sph) and is a substrate of SphK2 (15)(16)(17), there are no reported studies on the effect of FTY720 on the intrinsic balance of signaling sphingolipids. Metabolic interconnections between proapoptotic (ceramides) and prosurvival (dihydrosphingosine 1-phosphate (DHS1P)) molecules are expected because it is known that fumonisin B1 (FB1), an inhibitor of (dihydro)ceramide synthases, not only blocks the formation of ceramides and up-regulates the intracellular content of dihydrosphingosine (DHSph) but also increases the cellular level of DHS1P (19,20).…”
Section: Fty720mentioning
confidence: 99%